Współczesne poglądy dotyczące chirurgicznego leczenia stożka rogówki - Wyględowska-Promieńska, Dorota (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Keratoconus is a noninflammatory, progressive disease with ectasia and thinning of the corneal stroma, leading to decrease visual acuity related to asymmetrical irregular astigmatism and myopia. Currently, patients with keratoconus who are contact lens intolerant, are primarily treated by penetrating keratoplasty. When the cornea is transparent, other options may be considered. There are several studies about intrastromal rings implantation, in eyes with keratoconus. The major objective of corneal ring implantation is to reshape the abnormal cornea without removing corneal tissue or touching the central cornea.